Plating after tumor curettage in human femora does not efficiently improve torsional stability ex vivo - Vom Scheidt, Annika; Pirrung, Felix; Henyš, Petr; Oppelt, Birgit; Leithner, Andreas; Hammer, Niels; Bergovec, Marko (Journal of the mechanical behavior of biomedical materials, 2025)
BACKGROUND: Surgical treatments of benign primary bone tumors of the femur face the challenge of limiting tissue damage and contamination while providing sufficient stabilization to avoid fracture. While no clear treatment guidelines exist, surgical treatment commonly consists of femoral fenestration and curettage with optional filling and plating of the defect. Mono- or bicortical plating of distal femoral defects aim to reduce fracture risk and have been shown to increase axial stability. However, it remains unclear whether plating increases torsional stability of the affected femur. QUESTIONS/PURPOSES: This biomechanical study aimed to determine how much additional stability can be achieved by mono- or bicortical plating of femoral defects after fenestration. The following hypotheses were investigated: 1. Preventive plating of distal femur bone defects enhances torsional stability when compared to femoral fenestration alone. 2. A condition close to the intact (nonpathological) bone can be achieved by bone plating. 3. Defect shape influences torsional stability. PATIENTS AND METHODS: Thiel embalmed human femora (n = 24) were left intact or subjected to the following surgical treatments (A) defect creation via fenestration, (B) defect with short monocortical plating, (C) defect with long bicortical plating. All femora were torsion tested in midstance position using pre-cycling and testing until failure. Quantitative computed tomography pre and post testing allowed bone mineral density calculation and crack path analysis. Finite element analysis provided insight into defect shape variations. RESULTS: Torsion experiments showed no relevant enhancement of torsional stability due to mono- or bicortical plating. There were no significant differences in maximum torque between unplated and plated femora with defect (defect: 35.38 ± 7.53 Nm, monocortical plating: 37.77 ± 9.82 Nm, bicortical plating: 50.27 ± 9.72 Nm, p > 0.05). Maximum torque for all treatment groups was significantly lower compared to intact femora (155-200 Nm, p < 0.001). Cracks originated predominantly from the proximal posterior corner of the defect and intersected with screw holes in plated femora. The influence of variations of the defect corner shapes had no significant influence on maximum torque and angle. CONCLUSION: This biomechanical study shows that mono- or bicortical plating is not an effective preventive treatment against torsional failure of femora with distal defects as the resulting maximum torque was drastically reduced compared to intact femora. Thus, the initial hypotheses have to be rejected. As habitual loading of the femur includes a combination of axial and torsional loading, the observed lack of prevention against torsional failure might help to explain the occurrence of fractures despite plating. Future research towards ameliorating clinical outcome should address the role of defect filling with bone cement or bone grafts regarding the improvement of torsional stability after primary bone tumor treatment in the femur.
Keywords: mechanické testy; kyretáž; Female; ženské pohlaví; lidé; Curettage; Mechanical Tests; Torsion, Mechanical; Femur; torze mechanická; biomechanika; femur; Bone Plates; kostní destičky; Male; Aged; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Biomechanical Phenomena; Humans